2013
DOI: 10.3174/ajnr.a3801
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intracranial Hemorrhage in CT: Benefits of Sinogram-Affirmed Iterative Reconstruction Techniques

Abstract: BACKGROUND AND PURPOSE:Acute intracranial hemorrhage represents a severe and time critical pathology that requires precise and quick diagnosis, mainly by performing a CT scan. The purpose of this study was to compare image quality and intracranial hemorrhage conspicuity in brain CT with sinogram-affirmed iterative reconstruction and filtered back-projection reconstruction techniques at standard (340 mAs) and low-dose tube current levels (260 mAs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Several techniques for radiation dose reduction have been proposed (4)(5)(6)(7)(8)(9)(10)(11). Tube current modulation (TCM) adapts tube current to the body's anatomy in real-time and is activated on most currently available CT systems (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques for radiation dose reduction have been proposed (4)(5)(6)(7)(8)(9)(10)(11). Tube current modulation (TCM) adapts tube current to the body's anatomy in real-time and is activated on most currently available CT systems (12)(13)(14).…”
mentioning
confidence: 99%
“…Automated tube voltage adaptation (TVA) can adapt tube voltage to the patient body based on attenuation measurements, maintaining sufficient image quality, even in low-kilovoltage examinations. Furthermore, the application of iterative reconstruction (IR) techniques can substantially reduce image noise (4,(15)(16)(17).…”
mentioning
confidence: 99%
“…[4][5][6] The interaction of these parameters is complex, and manual adjustments may result in nondiagnostic images. Thus, commercially available techniques, including tube current modulation, 7 automatic exposure control, 8,9 automated tube voltage adaptation, 10,11 iterative reconstruction, [12][13][14][15] and selective in-plane shielding (thyroid, eye lens, breast, and gonads), 16 have been introduced to support the radiologic technologist, physicist, and radiologist team in developing appropriate CT protocols. Reduced tube voltage can increase contrast-to-noise ratio (CNR) of iodine enhancing soft-tissue structures, while the radiation dose is substantially reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported that the combination of a reduced tube voltage and an iterative reconstruction algorithm may allow substantial radia- tion dose reduction without impairment of image quality. [12][13][14]26 Third-generation DSCT has improved tube efficiency at lower tube voltages and is equipped with a model-based ADMIRE algorithm to provide adequate image quality in low-tube-voltage acquisitions. ADMIRE has been shown to provide an improved 3D regularization process, which results in better noise reduction in the image domain.…”
Section: 25mentioning
confidence: 99%
“…[7][8][9][10] The combination of such techniques with an iterative reconstruction algorithm can also provide similar image quality while substantially reducing exposure to ionizing radiation compared with the standard 120-kVp acquisitions. 11,12 Several studies have demonstrated that low-tube-voltage acquisitions at 80 kVp can increase iodine attenuation and image contrast of soft-tissue structures and reduce radiation exposure. [13][14][15] However, only a few studies have investigated low-tubevoltage acquisition CT techniques for imaging of the neck.…”
mentioning
confidence: 99%